Acute toxicity of soils contaminated with waste from an abandoned gold mine on seeds of Prosopis flexuosa and Larrea cuneifolia - Diaz, Pablo (2021)
The presence of metal(loid)s in soil causes toxicity in plants such as physiological disorders, and alterations in growth and development. The objective of this study was to evaluate the acute toxicity of soils contaminated with mining waste on seeds of Prosopis flexuosa (Pf) and Larrea cuneifolia (Lc), two native species from the Monte region (La Planta, San Juan, Argentina). Seeds were collected in the surroundings of La Planta and soil samples were taken in two sites: contaminated (S1) and reference sites (S2). Seeds were exposed to 6 increasing concentrations of soil mixtures from Site 1 and 2: 0, 10, 25, 50, 70, and 100% (v/v), where 0 corresponds to S2 soil and 100% to S1 soil. Experimental unit consisted of 20 seeds placed on wet soil into a Petri dish, reaching a total of 5 repetitions per treatment. A pre-germination treatment was applied to the seeds to ensure the seedling emergence. Toxicity test was carried out in a germination chamber in darkness at 25±2 °C. Due to differences in germination time of each species, exposure of Pf and Lc lasted 7 and 15 d, respectively. Mean germination time (MGT), germination index (GI), relative growth index (RGI) and IC50 of root (r) and hypocotyl (h) length were estimated. The concentration of the main metal(loid)s in soils were: S1) As=6608 mg kg-1 ; Zn=10892 mg kg-1 ; Cu=260 mg kg-1 ; Cd=90 mg kg-1 , and S2): Zn=46 mg kg-1 ; As, Cu and Cd were not detected. For Pf a significant increase in MGT was observed from treatment 70%, whereas a significant decrease in RGIr and RGIh, and GI were observed from 50% S1 concentration (p< 0.001). IC50r and IC50h were estimated in 21.1 and 40.3%, respectively. For Lc, seed germination inhibition of 100% was observed from 70% S1 concentration. Statistical differences between the values of RGIr, RGIh, and GI for remaining treatments were obtained (p< 0.001), while MGT showed no significant differences. The strongest inhibition was observed in 50% S1 concentration. IC50r and IC50h were estimated in 27.7% and 15.1%, respectively. The values of the toxicity endpoints and the phytotoxicity indexes showed that these native species are more tolerant to contaminated soil of La Planta than horticultural species evaluated in previous studies (IC50r < 1% S1 concentration). In future studies, chronic effects should be evaluated to determine the underlying physiological mechanisms of the metal(loid) tolerance in Pf and Lc.